Explosion temperature mapping of emulsion explosives containing TiH2 powders with the two-color pyrometer technique - Yu-Le Yao; Yang-Fan Cheng; Qi-Wei Zhang; Yu Xia; Fang-Fang Hu; Quan Wang; Yuan Chen (Defence Technology, 2022)
In the study, the two-color pyrometer technique was used to measure the transient temperature field of emulsion explosives with different contents of TiH2 powders. The experimental results showed that the introduction of TiH2 powders could significantly increase the explosion temperature and fireball duration of emulsion explosive. When emulsion explosives were ignited, the average explosion temperature of pure emulsion explosive continuously decreased while emulsion explosives added with TiH2 powders increased at first and then decreased. When the content of TiH2 powders was 6 mass%, the explosion average temperature reached its maximum value of 3095 K, increasing by 43.7% as compared with that of pure emulsion explosive. In addition, the results of air blast experiment and explosion heat test showed that the variation trends of shock wave parameters, explosion heat and theoretical explosion temperature of emulsion explosives with different contents of TiH2 powders were basically consistent with that of explosion temperature measured by the two-color pyrometer technique. In conclusion, the two-color pyrometer technique would be conducive to the formula design of emulsion explosive by understanding the explosion temperature characteristics.